Volatile constituents of the root and rhizome of Montrichardia linifera (Arruda) Schott (Araceae) - Batista, Raimundo Junior da Rocha; do Amarante, Cristine Bastos; Botelho, Anderson de Santana; Andrade, Eloisa Helena de Aguiar; do Nascimento, Lidiane Diniz (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2019)
The volatile constituents from the root and rhizome of Montrichardia linifera, collected in the Mangal das Garças mangrove (Belém, Pará), were obtained by simultaneous distillation extraction (SDE), and analyzed by gas chromatography-mass spectrometry (GC-MS), with the objective of contributing to the identification of constituents of the plant, subjected to two extraction times. A total of 42 volatile constituents were identified in the root, with Pentadecanal, Veratryl alcohol, Palmitic acid, and 2-Decanone as the major components. From the rhizome 38 constituents were identified, and the most significative were: Palmitic acid, Pentadecanal, Tetracosane, Dehydro-1,8-cineole, and Phytone. This is the first report on the volatile constituents of Montrichardia linifera.